Research on Adhesion Control Based on Optimal Creep Identification of High-speed Train - Yeqing WU; Xufeng ZHAO; Lizhi YU; Ke LI (机车电传动)
An optimal creep identification method was proposed for adhesion control of high-speed train, and the effectiveness of the method was verified by simulation analysis. Through the switching process of transient and steady-state control, the creep rate at the time of switching was captured as the control reference value, and the control reference value was adjusted by the fuzzy control method to identify the optimal creep rate of the track surface in real time. The method took the optimal creep rate as the control objective to obtain the optimal adhesion control effect, realized the utilization of adhesion coefficient, improved the stability of traction, and provided guidance for the application of adhesion control in the field of high-speed train.